Comparative trial of sulphasalazine and oral sodium cromoglycate in the maintenance of remission in ulcerative colitis. Issue 12 (December 1978) - Dronfield, M W; Langman, M J
Abstract : Patients with ulcerative colitis in remission were randomly allocated to treatment with sulphasalazine (2 g/day) or oral sodium cromoglycate (160 mg/day or 2 g/day), and the relapse rates in these treatment groups were compared during continued treatment for one year. The percentage cumulative relapse rate after 12 months' treatment was 30% in the 33 patients treated with sulphasalazine compared with 71% in the 25 treated with high dose sodium cromoglycate, a highly significant difference (P less than 0.01). Patients allocated low dose sodium cromoglycate were only treated for a maximum of six months, and the relapse rate in these 12 patients was similar to that in patients on the high dose. These results suggest that oral sodium cromoglycate is considerably less effective than sulphasalazine in maintaining remission, and by analogy with results in other trials may be no more effective than placebo tablets.